Pengembangan Media Big Book untuk Pembelajaran Membaca Permulaan di Kelas I SD Negeri - Anila Sitalawati; Titis Angga Rini; Sukamti Sukamti; Anila Sitalawati; Titis Angga Rini (Universitas Negeri Malang, 2022)
Abstract: Big book media for early reading learning was created because students still have obstacles in learning to read early. These obstacles come from some students who are not fluent in reading. In addition, the media used in students' initial reading learning is only in the form of a large black and white book that is less interesting and small writing so that students have difficulty in reading from a distance. This big book for early reading learning is to train students' early reading skills. This study aims to develop a big book media for valid early reading learning according to media experts, material expert and user, and also interesting for students. The research and development model used is ADDIE model whose stages include analysis, design, development, implementation, and evaluation. This study obtained the result of media expert validation of 98.4 percent, material expert validation of 91.6 percent, and user validation of 93.1 percent, so that it is included in the category of media is very valid and can be used in early reading learning. Based on the explanation above, it can be concluded that the big book media for early reading learning is very valid to use so that it can train students in reading early. Abstrak: Media big book untuk pembelajaran membaca permulaan dibuat karena siswa masih ada kendala dalam pembelajaran membaca permulaan. Kendala tersebut berasal dari sebagian siswa yang belum lancar membaca. Media yang digunakan dalam pembelajaran membaca permulaan siswa hanya berupa buku besar hitam putih yang kurang menarik dan tulisan yang kecil sehingga siswa kesulitan dalam membaca dari kejauhan. Media big book untuk pembelajaran membaca permulaan ini untuk melatih keterampilan membaca permulaan siswa. Penelitian ini bertujuan untuk mengembangkan media big book untuk pembelajaran membaca permulaan yang valid menurut ahli media, materi dan pengguna yaitu guru juga menarik untuk siswa. Model penelitian dan pengembangan yang digunakan yaitu model ADDIE yang tahapannya meliputi analisis, perancangan, pengembangan, implementasi, dan evaluasi. Penelitian ini memperoleh hasil validasi ahli media 98,4 persen, validasi ahli materi 91,6 persen, dan validasi pengguna 93,1 persen, sehingga termasuk dalam kategori media sangat valid dan dapat digunakan dalam pembelajaran membaca permulaan. Berdasarkan pemaparan diatas dapat disimpulkan bahwa media big book untuk pembelajaran membaca permulaan sangat valid digunakan sehingga dapat melatih siswa dalam membaca permulaan.